The prevalence of carpal tunnel syndrome in patients with epilepsy - Hicret Betul Akdag; Betul Cevik; Orhan Sumbul; Durdane Aksoy; Semiha Gulsum Kurt (Heliyon, 2024)
Objective: Carpal tunnel syndrome (CTS) is the most common type of entrapment neuropathy caused by compression of the median nerve in the carpal tunnel. Epilepsy is characterised by recurrent seizures caused by abnormal neuronal discharges in the brain.This study aimed to investigate whether there is a link between epilepsy and carpal tunnel and, if so, the underlying factors. Materials and methods: Two hundred patients with epilepsy were included in this study. The patients' history of epilepsy, seizure type, and seizure frequency were assessed. The Tinel, Phalen, and Flick physical examination tests were performed on patients with complaints that matched those of median nerve neuropathy. Patients with epilepsy and clinically diagnosed carpal tunnel syndrome completed the Boston Carpal Tunnel Syndrome Questionnaire, and nerve conduction studies were performed. The relationship between seizure type and frequency in patients with carpal tunnel syndrome was compared. Results: Compared to focal-aware motor-onset seizures, the risk of detecting carpal tunnel syndrome was 88.7 times higher in focal-onset bilateral tonic-clonic seizures. Patients with a seizure frequency of one per month or more had a 0.704 times lower risk of CTS than those with a frequency of one per week or more (p = 0.026). Discussion: Patients with epilepsy, especially those experiencing frequent seizures or specific seizure types, may be more susceptible to repetitive wrist flexion-extension postures. Therefore, during clinical follow-up, it is important to inquire about the presence of carpal tunnel syndrome in patients with epilepsy.